A TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material

By preparing TiB2-FeCoCrNiZr ceramic matrix composite material and using high-entropy alloy as the bonding phase, the problems of poor sintering performance and insufficient corrosion resistance of pure TiB2 are solved, and efficient sintering densification and significantly improved corrosion resistance of aluminum and liquid aluminum are achieved.

CN116334465BActive Publication Date: 2025-03-18XIANGTAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310222310.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-09
Publication Date
2025-03-18
Estimated Expiration
2043-03-09

AI Technical Summary

Technical Problem

Existing materials are susceptible to erosion during the corrosion process of liquid aluminum, resulting in deterioration of mechanical properties, increasing production costs and safety risks. Moreover, the sintering performance of pure TiB2 is poor, making it difficult to densify and sintering preparation.

Method used

The TiB2-FeCoCrNiZr ceramic matrix composite material was used to mechanically alloy Fe, Co, Cr, Ni, and Zr metal powders to form FeCoCrNiZr0.5 high-entropy alloy, and mixed with TiB2 powder to prepare by sintering. The high-entropy alloy is used as the bonding phase to improve the degree of sintering densification.

Benefits of technology

It significantly improves the material's resistance to liquid aluminum corrosion, reduces the temperature required for sintering and densification of TiB2-based ceramic materials, improves the overall sintering performance, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116334465B_ABST
    Figure CN116334465B_ABST
Patent Text Reader

Abstract

The invention discloses a TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material, wherein the FeCoCrNiZr is prepared by mechanical alloying of five metal element powders of Fe, Co, Cr, Ni and Zr. 0.5 The high entropy alloy powder is mixed with TiB2 powder, ball milled, dried and sintered to prepare the material. The aluminum liquid corrosion resistant material prepared by the invention is easy to prepare and has good corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of aluminum liquid corrosion resistant materials, and particularly relates to a TiB2-based composite material resistant to aluminum liquid corrosion. Background Art

[0002] Aluminum and aluminum alloys are widely used in aerospace, transportation, energy, electricity and other fields due to their excellent mechanical properties and corrosion resistance. However, as one of the most corrosive metal liquids, liquid aluminum can react with most metals to generate brittle intermetallic compound phases, affecting their comprehensive performance. In the production and processing of the aluminum industry, various production equipment and molds that are in direct contact with molten aluminum are deeply affected by the corrosion of molten aluminum. The generated corrosion products may not only enter the aluminum liquid and contaminate the product due to the deterioration of their mechanical properties, but are also more likely to cause the failure of production equipment, greatly increasing the production cost and safety risks of aluminum industry production. It can be said that the material's resistance to aluminum liquid corrosion is one of the important constraints on the development of the aluminum industry.

[0003] Therefore, it is necessary to prepare a new type of material resistant to aluminum liquid corrosion. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material, which is easy to prepare and has good corrosion resistance.

[0005] The technical solution of the present invention is as follows:

[0006] A method for preparing a material resistant to aluminum liquid corrosion comprises the following steps:

[0007] Step 1: Mix five metal powders of Fe, Co, Cr, Ni and Zr in a molar ratio of 1:1:1:1:0.5 and place them in a ball mill for mechanical alloying by wet ball milling. The ball milling aid is anhydrous ethanol, the ball milling speed is 250-300 r / min, and the ball milling time is 50-80 h. After each hour of ball milling, the ball mill is stopped for 20 minutes to cool. After the ball milling is completed, the obtained powder is placed in a vacuum drying oven for drying at a drying temperature of 60-80° C., a vacuum degree of -0.10 MPa, and a drying time of 18-24 h.

[0008] Step 2: FeCoCrNiZr obtained in step 1 0.5The high entropy alloy powder is mixed with the TiB2 powder and put into a ball mill for wet ball milling mixing treatment. The ball milling aid is anhydrous ethanol. The ball milling speed is 200-250r / min and the ball milling time is 8-12h. After each ball milling for 1h, the ball mill is stopped for 20min to cool down. After the ball milling is completed, the obtained powder is placed in a vacuum drying oven for drying treatment. The drying temperature is 60-80℃, the vacuum degree is -0.10MPa, and the drying time is 12-18h.

[0009] The mass proportion of TiB2 powder is 70% to 90%, and the corresponding FeCoCrNiZr 0.5 The mass percentage of the high entropy alloy powder is 30% to 10%.

[0010] Step 3: Place the dried TiB2-FeCoCrNiZr mixed powder obtained in step 2 into a mold for rapid hot pressing sintering at a sintering temperature of 1500°C, a heating rate of 100°C / min, a holding time of 5min, and a sintering pressure of 40MPa.

[0011] A ceramic matrix composite material resistant to aluminum liquid corrosion, composed of TiB2 powder and FeCoCrNiZr 0.5 It is prepared by mixing high entropy alloy powders and then sintering;

[0012] The mass proportion of TiB2 is 70% to 90%. 0.5 The mass percentage of the high entropy alloy component is 30% to 10%.

[0013] Beneficial effects:

[0014] The TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material disclosed in the present invention is prepared by mixing Fe, Co, Cr, Ni and Zr metal powders with preset percentages and performing mechanical alloying ball milling to prepare FeCoCrNiZr. 0.5 High entropy alloy powder, then FeCoCrNiZr 0.5 The high entropy alloy powder was mixed with TiB2 powder by ball milling, and finally TiB2-FeCoCrNiZr ceramic matrix composite was prepared by sintering. 0.5As a binder phase of composite materials, high entropy alloys can effectively reduce the temperature required for sintering and densification of TiB2-based ceramic materials, and effectively improve the overall sintering performance of TiB2-based ceramic materials. TiB2 has the advantages of high hardness, good wear resistance, and high-temperature oxidation resistance. In particular, it hardly reacts with molten aluminum at 700°C, making it an ideal material for resisting aluminum liquid corrosion. However, pure TiB2 has poor sintering performance and poor wettability with most metals, making it difficult to prepare by densification sintering. As an emerging metal material in recent years, high entropy alloys have a unique "high entropy effect" that helps to form a simple phase structure and helps to add ceramic-based composite materials as a binder phase to improve the overall densification degree. The "hysteresis diffusion effect" can further hinder the diffusion of aluminum into the material and improve the overall resistance of the material to molten aluminum corrosion.

[0015] Furthermore, the FeCoCrNiZr selected in the present invention 0.5 High entropy alloy system, the selected five metal elements Fe, Co, Cr, Ni, Zr, Ni, Zr react with aluminum at 700 ℃ to form simple Al3M type intermetallic compounds, the single structure of the reaction product is beneficial to the improvement of the overall anti-melting aluminum performance of the composite material, at the same time, the metal structure of Fe, Co, Ni has been shown to be FeCoCrNiZr x The high entropy alloy of the system has good mechanical properties and is an ideal material for the binder phase of TiB2 ceramic matrix composites.

[0016] At present, the average corrosion rate of cast iron materials commonly used in the production industry in 700℃ aluminum liquid is 8.5×10 -1 mm / h, the average corrosion rate of 316L stainless steel in 700℃ aluminum liquid is 1.1×10 -1 mm / h. However, the lowest corrosion rate of the 700℃ aluminum liquid of the material involved in the present invention is 1.868×10 -3 mm / h, compared with the aluminum liquid corrosion resistant materials commonly used in the current industry, the aluminum liquid corrosion resistant material in the example of the present invention has significantly improved aluminum liquid corrosion resistance. In addition, the material preparation method of the present invention is simple, the raw materials are easy to obtain, the overall production cost is low, and it has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a BSE-SEM image of the morphology and structure of the TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material in Example 1 of the present invention.

[0018] Figure 2 This is a BSE-SEM image of the morphology and structure of the TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material in Example 2 of the present invention.

[0019] Figure 3 This is a BSE-SEM image of the morphology and structure of the TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material in Example 3 of the present invention.

[0020] Figure 4 These are BSE-SEM images of the corrosion interface of the TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material in Example 1 of the present invention after being corroded in 700°C aluminum liquid for 2, 4, 6, 8, and 10 days.

[0021] Figure 5 These are BSE-SEM images of the corrosion interface of the TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material in Example 2 of the present invention after being corroded in 700°C aluminum liquid for 2, 4, 6, 8, and 10 days.

[0022] Figure 6 These are BSE-SEM images of the corrosion interface of the TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material in Example 3 of the present invention after being corroded in 700°C aluminum liquid for 2, 4, 6, 8, and 10 days.

[0023] Figure 7 Graph showing the change of corrosion depth over time of the TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material in three embodiments of the present invention. DETAILED DESCRIPTION

[0024] In order to facilitate the understanding of the present invention, the present invention will be described in more comprehensive and detailed manner below in conjunction with the accompanying drawings and preferred embodiments of the specification, but the protection scope of the present invention is not limited to the following specific embodiments.

[0025] Unless otherwise defined, all the technical terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The technical terms used herein are only for describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0026] Embodiment 1: A method for preparing a TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material, comprising the following steps:

[0027] (1) Sampling: Fe, Co, Cr, Ni, Zr and TiB2 powders were weighed according to the following mass percentage ratio: Fe powder 2.06%, Co powder 2.17%, Cr powder 1.92%, Ni powder 2.17%, Zr powder 1.68%, TiB2 powder 90%; the purity of the TiB2 powder used was 99.5%, and the particle size was 20 μm; the purity of the Fe, Co, Cr, Ni, and Zr powders used was 99.9%, and the particle size was 1 μm.

[0028] (2) Ball milling:

[0029] ① Mechanical alloying: Mix five metal powders of Fe, Co, Cr, Ni and Zr in a molar ratio of 1:1:1:1:0.5 and place them in a ball mill for mechanical alloying by wet ball milling. The ball milling aid is anhydrous ethanol, the ball milling speed is 250-300r / min, the ball-to-material ratio is 10:1, and the ball milling time is 50-80h. After each ball milling for 1h, the ball mill is stopped for 20min to cool down. After the ball milling is completed, the obtained powder is placed in a vacuum drying oven for drying treatment, the drying temperature is 60-80℃, the vacuum degree is -0.10MPa, and the drying time is 18-24h. The high entropy alloy powder obtained by ball milling should be a FCC+BCC mixed structure.

[0030] ② Mixing: FeCoCrNiZr obtained in step 1 0.5 The high entropy alloy powder is mixed with the TiB2 powder and put into a ball mill for wet ball milling and mixing treatment. The ball milling aid is anhydrous ethanol, the ball milling speed is 200-250 r / min, the ball-to-material ratio is 10:1, and the ball milling time is 8-12 h. After each hour of ball milling, the ball mill is stopped for 20 minutes to cool down. After the ball milling is completed, the obtained powder is placed in a vacuum drying oven for drying treatment. The drying temperature is 60-80°C, the vacuum degree is -0.10 to -0.16 MPa, and the drying time is 12 to 18 hours.

[0031] (3) Sintering: The dried TiB2-FeCoCrNiZr mixed powder obtained in step 2 is placed in a mold for rapid hot pressing sintering at a sintering temperature of 1500°C, a heating rate of 100°C / min, a holding time of 5 min, and a sintering pressure of 40 MPa. Figure 1 The following is a microstructure image of the TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material sample obtained in this embodiment under a scanning electron microscope (SEM). From the SEM image, it can be seen that the dark gray is the TiB2 hard phase, and between the TiB2 phases there are two high entropy alloy bonding phases, light gray and brighter, filling the gaps around the TiB2.

[0032] Among them, the sintering process used is rapid hot pressing sintering. Compared with traditional pressureless sintering and hot pressing sintering, this sintering process has a fast heating speed, low sintering temperature, and short sintering time. Compared with spark plasma sintering, it saves the expensive pulse power supply. The comprehensive preparation cost is relatively low, the sintered product quality is good, and the preparation efficiency is high. The sintering equipment used in the preparation can be FHP-808 rapid hot pressing sintering equipment or other equipment produced by Suzhou Hateng Technology Co., Ltd.

[0033] (4) Aluminum liquid corrosion resistance experiment: The round cake-shaped TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material sample (size: ) were cut into 5×5×10mm rectangular samples using a spark CNC wire cutting machine. The rectangular samples were then placed in a graphite crucible filled with 700°C molten aluminum for corrosion experiments. They were heated and kept warm using a pit-type resistance furnace and taken out after being corroded for 2, 4, 6, 8, and 10 days, respectively.

[0034] The corrosion depth and corrosion rate of TiB2-FeCoNiCrMn aluminum liquid corrosion resistant material samples at different times were calculated. This experiment used the depth method to measure the corrosion rate, and the calculation formula was: v = (ab) / 2t.

[0035] Where a is the thickness of the TiB2-FeCoCrNiZr aluminum molten corrosion resistant material sample before corrosion, b is the thickness of the TiB2-FeCoCrNiZr aluminum molten corrosion resistant material sample after corrosion, and t is the corrosion time. Before the molten aluminum corrosion experiment, a vernier caliper was used to measure the thickness before corrosion, and then the cross-sectional appearance of the TiB2-FeCoCrNiZr aluminum molten corrosion resistant material sample after corrosion was observed under a scanning electron microscope, and the remaining thickness b of the TiB2-FeCoCrNiZr aluminum molten corrosion resistant material sample after corrosion was measured using Smart TiffView software.

[0036] The final calculation shows that the corrosion rate of the TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material sample obtained in this embodiment is 1.868×10 -3 mm / h.

[0037] Figure 4 The SEM organization diagram of the microscopic morphology of the TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material sample obtained in this embodiment. The relationship between the corrosion depth of the TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material in this embodiment and time is as follows: Figure 7 shown.

[0038] Example 2: The method of Example 2 is the same as that of Example 1 except for step (1). Step (1) of Example 2 is as follows: Sample preparation: Fe, Co, Cr, Ni, Zr and TiB2 powders are weighed according to the following mass percentage ratio: Fe powder 4.12%, Co powder 4.35%, Cr powder 3.84%, Ni powder 4.33%, Zr powder 3.37%, TiB2 powder 80%; the purity of the TiB2 powder used is 99.5%, and the particle size is 20μm; the purity of the Fe, Co, Cr, Ni, and Zr powders used is 99.9%, and the particle size is 1μm; the remaining steps are the same as those of Example 1. The corrosion rate of the TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material sample obtained in this example is 8.531×10 -3 mm / h.

[0039] Figure 2The microstructure image of the TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material sample obtained in this embodiment under a scanning electron microscope (SEM). The relationship between the corrosion depth of the TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material in this embodiment and time is as follows: Figure 5 The relationship between the corrosion depth of the TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material in this embodiment and time is shown in the figure below. Figure 7 shown.

[0040] Example 3: The method of Example 3 is the same as that of Example 1 except for step (1). Step (1) of Example 3 is as follows: Sample preparation: Fe, Co, Cr, Ni, Zr and TiB2 powders are weighed according to the following mass percentage ratio: Fe powder 6.18%, Co powder 6.52%, Cr powder 5.75%, Ni powder 6.50%, Zr powder 5.05%, TiB2 powder 70%; the purity of the TiB2 powder used is 99.5%, and the particle size is 20μm; the purity of the Fe, Co, Cr, Ni, and Zr powders used is 99.9%, and the particle size is 1μm; the remaining steps are the same as those of Example 1. The corrosion rate of the TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material sample obtained in this example is 8.478×10 -3 mm / h.

[0041] Figure 3 The microstructure image of the TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material sample obtained in this embodiment under a scanning electron microscope (SEM). The relationship between the corrosion depth of the TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material in this embodiment and time is as follows: Figure 6 The relationship between the corrosion depth of the TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material in this embodiment and time is shown in the figure below. Figure 7 shown.

[0042] Figure 7 The following is a graph showing the corrosion depth of the three TiB2-FeCoCrNiZr aluminum liquid corrosion resistant materials in Examples 1, 2, and 3 versus time. It can be seen from the figure that under the same sintering temperature and TiB2 powder particle size, the TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material sample with 90% TiB2 content has better aluminum liquid corrosion resistance than the TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material samples with 80% TiB2 and 70% TiB2; and as time goes by, the corrosion rate of the TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material containing 90% TiB2 shows a decreasing trend. The average corrosion rate of the TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material obtained in Example 1 is calculated to be: 1.868×10 -3The average corrosion rate of the TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material obtained in Example 2 is: 8.531×10 -3 The average corrosion rate of the TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material obtained in Example 3 is: 8.478×10 -3 mm / h; compared with the corrosion rate of aluminum liquid corrosion resistant materials commonly used in industrial production, the corrosion rate of cast iron is about 0.85mm / h, and the corrosion rate of H13 steel is about 3.530×10 -2 mm / h. In the above embodiment, the aluminum liquid corrosion rate of the TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material is significantly reduced, and the aluminum liquid corrosion resistance is greatly improved.

[0043] The embodiments are only for facilitating the understanding of the technical solutions of the present invention and do not constitute a limitation on the protection scope of the present invention. Any simple modification, equivalent changes and modifications made to the above solutions that deviate from the contents of the technical solutions of the present invention or based on the technical essence of the present invention are still within the protection scope of the present invention.

Claims

1. A TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material, characterized in that: TiB2 powder and FeCoCrNiZr 0.5 The high entropy alloy powders are mixed and then ball milled, dried and sintered; wherein the mass percentage of the TiB2 powder is 90%, and the mass percentage of the FeCoCrNiZr 0.5 The mass percentage of high entropy alloy powder is 10%; The FeCoCrNiZr 0.5 The components of the high entropy alloy powder raw material in the TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material are as follows: Fe powder 2.06%, Co powder 2.17%, Cr powder 1.92%, Ni powder 2.17%, Zr powder 1.68%; The FeCoCrNiZr 0.5 High entropy alloy powder is made of Fe, Co, Cr, Ni, and Zr metal powder by mechanical alloying method; The TiB2 powder has a purity of 99.5% to 99.9% and a particle size of 20 μm; The purity of the Fe powder, Co powder, Cr powder, Ni powder and Zr powder is 99.9% to 99.99% and the particle size is 1 μm; The sintering adopts rapid hot pressing sintering; The rapid hot pressing sintering means: placing the dried powder in a mold, heating it to a temperature T of 1500°C at a heating rate of 100°C / min, and keeping it at the temperature T for 5 to 10 minutes at a pressure of 40 MPa.

2. The TiB2-FeCoCrNiZr aluminum liquid corrosion resistant material according to claim 1, characterized in that: The mechanical alloying method comprises the following steps: placing Fe, Co, Cr, Ni and Zr metal powders in a molar ratio of 1:1:1:1:0.5 into a ball mill, using anhydrous ethanol as a ball milling aid, and performing wet ball milling; the ball-to-material ratio used in the ball milling is 10:1, the rotation speed is 250-300 r / min, and the ball milling time is 50-80 h, wherein the ball mill is stopped for 20 min for every 1 h of ball milling; and then placing the powder obtained by ball milling into a vacuum drying oven for drying treatment, the drying temperature is 60-80°C, the vacuum degree is -0.10 MPa, and the drying time is 18-24 h.

Citation Information

Patent Citations

  • Titanium carbonitride based metal ceramic based on high-entropy alloy binder phase and preparation method of metal ceramic

    CN102787266A

  • TiB2-Fe-Co-Ni-Cr liquid aluminum corrosion-resistant material

    CN111004955A